The Impact of Profitability, Financial Fragility and Competitive Regime Shifts on Investment Demand: Empirical Evidence - James Crotty; Jonathan Goldstein (Levy Economics Institute of Bard College, 1992)
Crotty and Goldstein have developed a hybrid post-Keynesian/ neo-Schumpeterian theory of investment demand. In this micro-founded theory of accumulation, the optimal investment decision depends on the level of expected profitability, the degree of competition, and the degree of financial fragility. Its core assumptions are: i)the future is unknowable in principle, ii) physical capital is ii) illiquid and the accumulation process is substantially irreversible, iii) managers and owners are distinct economic agents with an unresolved principal-agent conflict, and iv) management seeks the long-term growth and financial stability of the firm itself, and guards its decision-making authority against encroachment by stockholders and creditors. In this model, there is an unavoidable growth-safety tradeoff: the firm's drive for growth and profits is constrained by management's desire for financial security and decision-making autonomy. In this paper, Crotty and Goldstein seek to provide empirical support for their earlier model through a polynomial-distributed lag regression analysis of the determinants of the rate of accumulation in the U.S. manufacturing sector between 1954 and 1988. The manufacturing sector was chosen as affording the best test of the Schumpeterian competition effect. The authors test econometrically for the presence of regime shifts at the end of the 1960s and the beginning of the 1980s-two periods in which foreign competition appears to have increased significantly. The econometric results establish a strong Schumpeterian competition effect, in which intensified competition compels firms to undertake additional investment to defend existing illiquid capital. In addition, there is strong support for the notion of a post-Keynesian growth/financial security/autonomy tradeoff in the determination of the level of investment. Finally, the profit rate/competition/financial security nexus allows the authors to explain important trends in the post-war accumulation of capital.
Keywords: 330